MARKET OVERREACTION AND PRICE REVERSALS IN JAKARTA STOCK EXCHANGE - Askardiya R. Adjie (LP2M Sekolah Tinggi Ilmu Ekonomi IPWI Jakarta, 2017)
This paper provides a comprehensive examinations of short run market overreaction and price reversals at Jakarta Stock Exchange from April 1997 to August 2006 and performs stock forecasting to predict the trend line using two kind of technique that is moving average and exponential moving average. Moreover, researcher test investor’s possibility to profit from overreaction phenomenon conducted by comparing cumulative abnormal return of loser stock with average relative bid ask spread using t-test for paired data and by applying simple trading rule. The result does not indicate significant price reversal of winner stocks on first day after the event date, but loser stock experience positive abnormal return one day after the event. From profit making perspective, the result indicates that after considering transaction cost traders can not earn profit from these reversals. Key words:Market Overreaction, Price Reversals